IMPLEMENTASI KEBIJAKAN PENGELOLAAN AIR LIMBAH DOMESTIK DI KABUPATEN NATUNA - KUSNAIDI, KUSNAIDI (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
Indonesia's rapid population growth, particularly in urban areas, has a significant impact on the environment's carrying capacity. Similarly, the current wastewater problem in Natuna Regency is a project that needs to be undertaken right away by the local government, which, of course, necessitates the cooperation of all parties as well as considerable funding. The purpose of this study is to look at how domestic wastewater management policies are implemented in Natuna Regency. This research used qualitative research with descriptive methods.  The theory used is the theory of public policy and public policy implementation. The study's results indicate that the Natuna Regency Wastewater Management Unit's communication, disposition, and bureaucratic indicators have been performing effectively, while the resource indicators continue to face challenges and budgetary constraints. In the meantime, the money and the community's lack of awareness of clean living are stumbling blocks to the adoption of domestic wastewater management rules.